Stories as a Pedagogical Tool for Teaching-Learning of Basic Astronomy - Chopra, Shruti; Sasan, Abhishreya (Voices of Teachers and Teacher Educators, 2021)
The study explored the influence of story-telling on primary grade learners’ intuitive conceptions about the relative movement of the Sun, Earth and Moon (SEM) and related phenomena (day and night, phases of moonMoon). It was observed that learners possessed a great deal of narratives heard or read from various sources as Sun, Moon and other planets are deemed to be of religious importance in the Indian context. These alternative conceptions differed significantly from scientifically accepted conceptions. Also, learners had little to no understanding of the actual cause cause-and and-effect relationship involved in the phenomena. Designing and enactment of modules to address these preconceptions using story-telling as a pedagogical strategy enabled learners to establish scientifically accepted conceptions, which were assessed using questionnaires and rubrics.